GAYA BAHASA PADA LIRIK LAGU ALBUM MENGUDARA KARYA IDGITAF - Windarti, Dewi Khusda; Heryana, Nanang; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This study aims to describe the style of comparative language; opposing language styles; linking language style; and the repetitive language style in the lyrics of the album Mengudara by Idgitaf. Language style is a variety of expressions of using language to obtain certain effects and has characteristics in conveying thoughts and feelings, both orally and in writing. Recently, the Indonesian music world has emerged many new musicians who are characterized by the lyrics they create and the way they deliver unique and impressive songs. One of the many Indonesian musicians who use word games in their lyrics is Brigitta Sriulina Beru Meliala or commonly known as Idgitaf. Idgitaf is a singer, songwriter, and content creator who started her career in 2020. This study uses a descriptive method in the form of qualitative research. The data collection technique uses observation techniques and documentary studies. This research found several types of language styles in the lyrics of the song album Mengudara by Idgitaf. The types of language styles in this study are: First, comparative language styles: simile language styles, metaphorical language styles, personification language styles, and antithesis language styles. Second, the language style of opposition: Hyperbolic language style, litotes language style, and irony language style. Third, linkage language styles: erotic language styles, parallelism language styles, ellipsis language styles, and gradient language styles. Fourth, repetitive language styles: Assonance language styles, anaphoric language styles, and epistrophic language styles.